(untitled) (Academic Journal of Internal Affairs, 2020)
In the 21st century rapid changes in the world of work and fast developments and changes posed a range of challenges for both organizations and leaders. The agencies have to adapt increasingly to the fast-changing global environment and to local challenges. This study intends to answer what kind of leadership style can be effective. I review the external and internal environmental factors and their effects on the operation of organizations. I focused on the vision and workplace needs of each generation at a workplace. I attempt to focus on the challenges arising from the different approaches of the generations and try to summarize the opinions and expectations of current public service leaders. In this study I present some research results of both the administrative and the law enforcement area on a similar topic. Finally, I try to find a solution to the challenges arising from the approach and expectations, I briefly discuss the methodology of team coaching and the possibility of introducing it in the public service.